Effect of soft reduction technique on microstructure and toughness of medium carbon steel. (March 2021) - Ali, Naqash; Zhang, Liqiang; Zhou, Hongwei; Zhao, Aonan; Zhang, Chaojie; Fu, Kaixuan; Cheng, Jinqi
Abstract: This paper investigated the effect of soft reduction technique on microstructure evaluation and toughness of medium carbon steel. The scanning electron microscope (SEM) was used in conjunction with fracture test to identify the comparative microstructure-toughness relationship, while the morphology of grain boundary ferrite (GBF) and widsmanstatten ferrite (WF) was analyzed by electron backscatter diffraction (EBSD) at different soft reduction amounts. It was observed that the area ratio of grain boundary ferrite phases (GBF + WF) decreases with increasing the reduction amount. Both ferrite phases nucleated at the austenite grain boundary and grow into their neighbouring grain due to the different orientation relationship. At high reduction amounts the GBF holds non K-S orientation with prior austenite grain into which it grows, caused by the presence of high energy interface between the GBF and martensite matrix. This criterion restricts the formation of GBF along the prior austenite grain boundary (PAGB) and resulting in its discontinuous growth into the adjacent austenite grain. The continuous grain boundary ferrite precipitation is more detrimental as compared to the discontinuous precipitation. Furthermore, film-like retained austenite was aligned along the growth direction of widsmanstatten ferrite plates with its increased volume fraction at high reduction amounts, which manifested the improved fracture toughness.